Nevirapine Dosing For Treatment In The First Month Of Life - Mirochnick, Mark; Capparelli, Edmund V.; Nielsen, Karin; Pilotto, Jose Henrique; Musoke, Philippa; Shetty, Avinash; Luzuriaga, Katherine (In Conference on Retroviruses and Opportunistic Infections (CROI), 2016)
NVP clearance (CL) is low in term neonates and further decreased in premature infants due to immaturity in CYP2B6 and CYP3A4 activity. NVP autoinduces its own CL but the extent of autoinduction on immature enzyme systems is unknown. While pharmacokinetic (pk) studies have been done to determine NVP dosing regimens for treatment of HIV infection (trough conc target 3.0 ug/mL) in infants after 1 month of life, NVP pk studies under age 1 month have been limited to evaluations of dosing regimens for prophylaxis against HIV infection (trough conc target 0.1 ug/mL). Population modeling of these pk data and simulations can be used to evaluate proposed NVP dosing regimens to meet treatment target conc in term and late preterm infants (34-37 weeks gestation) from birth through 6 months of life. We developed a NVP population pk model using NONMEM that incorporated data for 192 infants (1121 plasma NVP conc) from US, Africa and Brazil under age 1 yr in 5 PACTG or HPTN protocols. Dosing regimens from birth through 6 months of age were evaluated using simulations. Simulated NVP doses included 6 mg/kg BID for term infants and 4mg/kg BID for 1 week followed by 6 mg/kg BID for late preterm infants. Proposed PK target was NVP trough conc > 3.0 ug/mL. A one compartment model with first order absorption was used. CL was scaled allometrically and volume of distribution (Vd) was scaled linearly for weight. CL was modeled to mature exponentially with age. Autoinduction of CL was modeled as a linear function of dose. The effects of prematurity and maturation of CYP2B6 and CYP3A4 activity on NVP CL were imputed from published studies. Typical CL (L/hr/kg) in term infants increased by nearly 6 fold from birth to 6 months due to maturation and by an additional 79% due to induction. Final simulations used term infant doses of 6 mg/kg BID and late preterm infant doses of 4mg/kg BID for 1 week followed by 6 mg/kg BID. In these simulations, the dosing regimens achieved the NVP trough target. NVP CL is low immediately after birth and increases dramatically over the 1st months of life. Appropriate NVP dosing regimens in neonates must take into account the impact of maturation, autoinduction and prematurity on NVP CL. The dosing regimens supported by these simulations and NVP PK in preterm infants are being studied in the IMPAACT 1115 and 1106 protocols